Cardioprotective effects of curcumin against myocardial I/R injury: A systematic review and meta-analysis of preclinical and clinical studies - Li, Tianli; Jin, Jialin; Pu, Fenglan; Bai, Ying; Chen, Yajun; Li, Yan; Wang, Xian (Frontiers in Pharmacology, 2023)
Objective: Myocardial ischemia-reperfusion (I/R) injury is a complex clinical problem that often leads to further myocardial injury. Curcumin is the main component of turmeric, which has been proven to have many cardioprotective effects. However, the cardioprotective potential of curcumin remains unclear. The present systematic review and meta-analysis aimed to evaluate the clinical and preclinical (animal model) evidence regarding the effect of curcumin on myocardial I/R injury Methods: Eight databases and three register systems were searched from inception to November 1, 2022. Data extraction, study quality assessment, and data analyses were carried out strictly. Then a fixed or random-effects model was applied to analyze the outcomes. SYRCLE's-RoB tool and RoB-2 tool was used to assess the methodological quality of the included studies. RevMan 5.4 software and stata 15.1 software was used for statistical analysis. Results: 24 animal studies, with a total of 503 animals, and 4 human studies, with a total of 435 patients, were included in this study. The meta-analysis of animal studies demonstrated that compared with the control group, curcumin significantly reduced myocardial infarct size (P < 0.00001), and improved the cardiac function indexes (LVEF, LVFS, LVEDd, and LVESd) (P < 0.01). In addition, the indexes of myocardial injury markers, myocardial oxidation, myocardial apoptosis, inflammation, and other mechanism indicators also showed the beneficial effect of curcumin (P < 0.05). In terms of clinical studies, curcumin reduced the incidence of cardiac dysfunction, myocardial infarction in the hospital and MACE in the short term, which might be related to its anti-inflammatory and anti-oxidative property. Conclusions: Our study is the first meta-analysis that includes both preclinical and clinical researches. We demonstrated that curcumin plays a cardioprotective role in acute myocardial infarction in animal studies mainly through anti-oxidative, anti-inflammatory, anti-apoptosis, and anti-fibrosis effects. In addition, from the clinical studies, we found that curcumin might need a longer course of treatment and a larger dose to protect the myocardium, and its efficacy is mainly reflected in reducing the incidence of myocardial infarction and MACE. Our finding provides a novel opinion for further research.